THE EFFECTIVENESS OF FISCAL POLICY AND GOVERNMENT STIMULUS IN MAINTAINING DOMESTIC CONSUMPTION AND INVESTMENT: A LITERATURE REVIEW - Gunawan Widjaja (Review of International Economy and Finance, 2025)
This article aims to review the effectiveness of fiscal policy and government stimulus in maintaining domestic consumption and investment, particularly during periods of economic crisis. Through a literature review, it was found that fiscal policy instruments such as government spending, tax incentives, and social assistance play a significant role in maintaining people's purchasing power and encouraging investment recovery. The success of stimulus measures is highly influenced by the speed of distribution, targeting accuracy, and the fiscal capacity of the country concerned. However, the implementation of fiscal policies also faces various challenges such as limited fiscal space, the risk of rising public debt, bureaucratic weaknesses, and the need for transparent governance. The review emphasises the importance of adaptive stimulus design, synergy with monetary policy, and continuous evaluation to ensure that fiscal policy remains effective and sustainable in the face of future global and domestic economic dynamics.